Frequency and Outcomes of Arrhythmias - Zulfiqar Ali ,Muhammad Masood Khokhar,Sosan Shahid, Shahid Mahmood ,Sohail Tufail, (Journal of Rawalpindi Medical College, 2013)
Background: To determine the types, characteristics, treatment and outcome of cardiac tachyarrhythmias. Methods: In this cross sectional study, 78 patients with symptomatic cardiac tachyarrhythmias were assessed for age, sex, associated cardiovascular risk factors and treatment options. Monitoring was done for cardiac tachyarrhythmias at presentation or during hospital stay with documentation of the arrhythmias from the cardiac monitor memory and/or instant 12-lead ECG. Results: Mean age was 57.1 years. Male to female ratio was 1.38:1. Major cardiovascular risk factors were encountered in 58% of the patients. Tachyarrhythmias occurred in 42% patients without any associated risk factor. Only 28% of patients with ventricular tachycardia (VT) were managed with drugs alone. Defibrillation was required in all the patients with ventricular fibrillation (VF). All the patients with pulseless VT (33%) were defibrillated but the stable VT with pulse were treated with antiarrhythmic drug (28%) and unstable VT with pulse (72%) received synchronized cardioversion. The patients with SVT were treated with drugs alone (33%), drugs followed by cardioversion (45%) and cardioversion alone (22%). Inj. Verapamil 5 mg (either alone or prior to cardioversion) was given to 78% patients with SVT as compared to cardioversion alone (22%). Verapamil was given as monotherapy (43%), verapamil + beta blockers (29%), verapamil + amiodarone (21%), and combination of all three antiarrhythmic drugs to 7% patients. Pharmacological therapy was also offered to patients who presented with stable AF with fast ventricular rate, which included beta blockers 50% (4/8), amiodarone to 12.5% (1/8), digoxin to 25% (2/8), and combination of beta blockers and amiodarone 12.5% (1/8) patients. Conclusion: Wide complex tachyarrhythmias like ventricular tachyarrhytmias and ventricular fibrillation are common. Electrical therapy is a preferred choice to treat any form of tachyarrhythmia. Atrial fibrillation is the most treatment-resistant tachyarrhythmia.